Composition dependent properties of graphene (oxide)‐alginate biopolymer nanocomposites. (11th October 2016) - Vilcinskas, Karolis; Jansen, Kaspar M.B.; Mulder, Fokko M.; Picken, Stephen J.; Koper, Ger J.M.
Abstract : We report on the thermal, electrical, and mechanical properties of alginate biopolymer nanocomposites prepared by solution casting with various amounts of graphene oxide (GO) or reduced GO (rGO). Our data shows that the thermal stability of alginate nanocomposites can be improved by the introduction of cross‐linking through divalent metal cations, albeit that under these conditions little influence by the amount of rGO remains. On the other hand, the electrical conductivity of divalent metal ion cross‐linked‐rGO improves approximately 10 orders of magnitude with increasing weight fraction of rGO, whereas it declines for sodium alginate‐GO composites. In addition, storage moduli and glass to rubber transition temperatures show strong composition dependence as a consequence of complex interactions of the ions with both polymer and filler. We propose a mechanical model that allows for the accurate prediction of reinforcement by GO sheets in sodium alginate‐GO composites taking into account the orientational order of the sheets. Creep tests reveal the complex nature of multiple stress relaxation mechanisms in the nanocomposites although the stretched exponential Burgers' model accurately describes short time creep compliance. POLYM. COMPOS., 39:E236–E249, 2018. © 2016 Society of Plastics Engineers